The expanding field of IgG4‐mediated neurological autoimmune disorders. (29th May 2015) - Huijbers, M. G.; Querol, L. A.; Niks, E. H.; Plomp, J. J.; van der Maarel, S. M.; Graus, F.; Dalmau, J.; Illa, I.; Verschuuren, J. J.
<x xml:space="preserve">Abstract</x> At least 13 different disease entities affecting the central nervous system, peripheral nervous system and connective tissue of the skin or kidneys are associated with immunoglobulin G4 (IgG4) immune reactivity. IgG4 has always been considered a benign, non‐inflammatory subclass of IgG, in contrast to the well‐known complement‐activating pro‐inflammatory IgG1 subclass. A comprehensive review of these IgG4 autoimmune disorders reveals striking similarities in epitope binding and human leukocyte antigen (HLA) associations. Mechanical interference of extracellular ligand−receptor interactions by the associated IgG4 antibodies seems to be the common/converging disease mechanism in these disorders.